A novel reduced column section approach for the seismic protection of wind turbines. (1st May 2023) - Rostami, Rohollah; Tombari, Alessandro
Abstract: The rapid increase in global energy demand over the coming decades must be sustained by a more consistent increment of energy production from renewable sources of which wind energy is currently one of the fast-growing resources. New onshore and offshore wind farms will be rapidly constructed in challenging environments, especially in earthquake-prone areas. As a result, the mitigation of the dynamic vibrations of the wind turbines becomes a fundamental aspect of the seismic design to guarantee their normal operativity and structural safety. Different from past proposals based on traditional passive control devices such as tuned mass dampers or tuned liquid column dampers, this study aims to propose a novel approach, the Reduced Column Section (RCS), to derive an innovative mitigation device which replaces the traditional transition piece of the wind turbine. Analytical formulas to design the proposed RCS will be established. The benefits of the proposed device will be assessed on a real onshore wind turbine located in Italy. Modal properties obtained from the continuous dynamic monitoring of the wind turbine will be used to characterize the numerical finite element model. Therefore, a direct integration analysis with spectrum-compatible real earthquakes and an incremental dynamic analysis will be conducted to evaluate the dynamic mitigation induced by the proposed RCS. Soil-structure interaction effects will be also considered. This study shows that RCS can efficiently mitigate the effective stresses on the wind tower wall by up to 70% compared to the stresses computed on the existing structure. Highlights: A Reduced Column Section approach used to derive an innovative transition piece for onshore wind turbines is established. Analytical formulas for the design of the novel Reduced Column Section are provided. A dynamic monitor system is installed in an existing onshore wind turbine located in Italy. The impact of the Reduced Column Section on mitigating the structural vibrations induced by earthquakes is assessed. Relevant mitigation of the effective stresses (up to 70% reduction) on the tower wall is achieved.